Updates and reflections about the IJHPR, on the eve of its seventh year - Bruce Rosen; Avi Israeli (BMC, 2017)
Abstract The Israel Journal of Health Policy Research (IJHPR) will soon be completing 6 years of publication. During this period, it has published well over 300 articles and has become a stable and vital part of Israeli health care. The number of IJHPR articles published annually has increased significantly over time, and the number of submissions has increased even more significantly. The journal is regularly drawing submissions from a very broad range of Israeli universities, hospitals, health plans, and other institutions, and from leading institutions abroad. The journal's articles cover a wide spectrum of subjects related to health policy, as reflected in the diversity of the article collections that the journal has launched to date. True to its mission statement, the IJHPR is promoting "intensive intellectual interactions among scholars and practitioners from Israel and other countries regarding all aspects of health policy". The journal has been indexed in all of the leading international academic databases and its current impact factor (1.36) puts it in the third quartile in two key Web of Science subject categories. Several IJHPR articles have been accessed over 10,000 times and the IJHPR has become the predominant vehicle in which Israeli scholars are publishing articles with a health policy orientation. IJHPR articles are also figuring prominently in many course syllabi in Israel, and Israeli universities have incorporated IJHPR publications into assessments of faculty members for promotion. The journal's success and progress are a part of a larger trend of greater reliance on data and analysis in health policymaking in Israel and the increasing prominence of health in the Israeli policy agenda and public discourse. During the journal's seventh year, its editors will be carrying out a serious assessment of the challenges and opportunities ahead and developing an updated plan for the journal's development. In doing so, they will draw on data presented in this editorial as well as on in-depth discussions with those who have contributed to the journal's success to date: it publisher, sponsor, and editorial board members, as well as a sample of authors, reviewers and readers. The expectation is that, by working together, it will be possible to take the journal to new heights.